HOW TO DEFINE AN ORGANIZATION’S MATURITY FOR ADOPTING ARTIFICIAL INTELLIGENCE SOLUTIONS - Jaaksi, Juha (My University, 2018)
Artificial intelligence (AI) is the most anticipated technology to date. Proven to increase value on a multitude of business enterprises, nations and private organization are racing to develop and adopt the most sophisticated AI solutions. Even as funding for development surges, few organizations comprehend how to properly implement AI solutions. The following thesis investigates the requirements for an organization to adopt AI solutions. Additionally, it provides a tool for evaluating maturity and readiness for adopting AI solutions. The investigation was conducted in a large organization, data was collected with semi-structured themed interviews and analyzed by grounded theory research methodology. The study involved eight (8) respondents from the investigated organization and three (3) experts from renowned consulting organizations. The literature review was conducted by studying the research of acknowledged articles and advocated literature from the AI experts and community. The study concluded the most significant enablers for organizations to adopt AI solutions are: availability of the training data, workforce abilities and experience, organizational status on current AI solutions, as well as mentality and future ambitions. The results implicate that the organizations should focus on development of their workforce abilities and experience on modern AI tools and methods. Moreover, the organization must be able to collect, transfer and store the data in the means of quality and quantity. Furthermore, the data availability and usability must be well assessed. Therefore, employees can access data effortlessly and process data according to the data privacy and security policies.
Keywords: Artificial Intelligence, Machine Learning, Intelligent Automation, Machine Intelligence